Digital Design and Computer Architecture - Harris, David Money; Harris, Sarah L. (Elsevier, 2007)
This book is designed for courses that combine digital logic design with computer organization/architecture or that teach these subjects as a two-course sequence. The book begins with a modern approach by rigorously covering the fundamentals of digital logic design and then introduces Hardware Description Languages (HDLs). Featuring examples of the two most widely-used HDLs, VHDL and Verilog, the first half of the text prepares the reader for the design of a MIPS processor which is discussed in the second half of the book. By the end of the book, readers will be able to build their own microprocessor and will have a top-to-bottom understanding of how it works, even if they have no formal background in design or architecture beyond an introductory class. The authors combine an engaging and humorous writing style with an updated and hands-on approach to digital design.